Severe Degenerative Changes in Cryptorchid Testes in Japanese Black Cattle. Issue 3 (May 2020) - Fuke, Naoyuki; Kitahara, Go; Ito, Soma; Van Diep, Nguyen; Ping Teh, Angeline Ping; Izzati, Uda Zahli; Myint, Ohnmar; Hirai, Takuya; Torisu, Shidow; Kaneko, Yasuyuki; Sato, Hiroyuki; Hidaka, Yuichi; et al.
This is a histopathologic and endocrinologic study of 6 calves diagnosed with cryptorchidism. Cases 1–3 were diagnosed as resembling testicular regression syndrome. In cases 1 and 2, the extracted tissue was a small, firm, gray-white mass, and there was lack of obvious testicular tissue in case 3. Histopathologically, the excised tissue in cases 1–3 was a fibrotic testicular remnant with inflammation, mineralization, hemosiderin-laden macrophages or lipofuscin-laden macrophages, and lack of germ cells and interstitial endocrine cells. These findings were compared with cases 4–6, which were diagnosed as testicular hypoplasia due to cryptorchidism. These cases had small but otherwise grossly unremarkable intra-abdominal testicular tissue and histologically had a few germ cells and sustentacular cells with arrested spermatogenesis and an increase in interstitial endocrine cells. Cases 1–3 had more severe degenerative changes compared with cases 4–6. In case 2, the average diameter of the seminiferous tubules was much smaller than in cases 4–6, and there were few tubule cross sections. Anti-Müllerian hormone (214 pg/ml) was detected in the plasma of case 2. Based on the macroscopic and histopathologic findings as well as endocrinologic profiles, the testicular degeneration in cases 1–3 was considered similar to that of testicular regression syndrome. In this condition, it is thought that a normally developing intra-abdominal testis undergoes degeneration due to heat or a vascular disorder such as torsion.